Effects of Cognitive Flexibility, Prosocial and Problem Behaviours, Parenting Style and Social Support on Social Adaptation Among Children With Leukaemia: A Structural Equation Modelling Approach - Mengjia, Wang; Jinjin, Lei; Jinglan, Ji; Dan, Li; Nan, Qin; Ruixing, Zhang (Journal of clinical nursing, 2025)
ABSTRACT Background Leukaemia children often encounter various social adaptation issues stemming from changes in their living environment. Identifying and optimising the factors associated with social adaptation is crucial in improving social adaptation in children with leukaemia. Objectives To investigate social adaptation in children with leukaemia and to clarify the impact pathway of cognitive flexibility, problem behaviour, prosocial behaviour, parenting style and social support on social adaptation. Methods Using a convenience sampling method, 264 leukaemia children completed a cross‐sectional survey. Data were collected using the Social Adaptation Assessment Scale for Children with Leukaemia, Strengths and Difficulties Questionnaire, Cognitive Flexibility Scale, Short‐Egna Minnenav Barndoms Uppfostran and Multi‐Dimensional Scale of Perceived Social Support. Structural equation modelling was used to test the influencing factors of social adaptation. Results Social support directly influenced social adaptation (β = 0.19, p < 0.01) and indirectly influenced social adaptation through prosocial behaviour (β = 0.06, p < 0.01) and problem behaviour (β = 0.18, p < 0.01). Prosocial behaviour (β = 0.17, p < 0.01) and problem behaviour (β = −0.61, p < 0.01) directly influenced social adaptation. Negative parenting directly influenced social adaptation (β = 0.12, p < 0.01) and indirectly influenced social adaptation (β = −0.23, p < 0.01) through problem behaviour. Conclusion Our finding indicated that there are prominent social adjustment problems in the recovery process of children with leukaemia. These findings suggest that targeted education is needed to enhance social adaptation among children with leukaemia. Relevance to Clinical Practice The final model should serve as a framework to guide intervention research targeting social support and negative parenting to improve the social adaptation of children with leukaemia. During the recovery process, nurses need to regularly follow up on the children's social adaptation and encourage them to participate in social activities to increase social support while providing family guidance based on improving parenting styles. Patient or Public Contribution The subjects of this study were children with leukaemia aged 8–18 years. All authors read and approved the final manuscript.